(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The middle graph of a graph G, denoted by is a graph whose vertex set is and two vertices are adjacent if they are adjacent edges of G or one is a vertex and other is an edge incident with it. A dominating set D of is called a connected dominating set of if the induced subgraph is connected. The minimum cardinality of D is called the connected domination number of and is denoted by .